Study of Demarcation Line Depth in Transepithelial versus Epithelium-Off Accelerated Cross-Linking (AXL) in Keratoconus - Yehia Salah; Kholoud Omar; Ahmed Sherif; Sarah Azzam (Journal of Ophthalmology)
Aim. This is a prospective interventional clinical trial to assess the depth of the demarcation line in transepithelial versus epithelium-off accelerated corneal cross-linking (AXL) in keratoconus patients. Methods. This prospective clinical trial was conducted on 40 eyes of 20 patients. Each patient had transepithelial AXL in one eye and epithelium-off AXL in the contralateral eye applying UVA light with an irradiance of 45 mW/cm2 for 2.4 minutes and 30 mW/cm2 for 4 minutes. The depth of the demarcation line was measured using anterior segment OCT (Topcon 3D OCT-2000) one month postoperative for both eyes. Results. The demarcation line was patchy in 50% of the transepithelial AXL eyes, the other half showing a demarcation line at a mean depth of 183 ± 41.6 μm. In the epithelium-off AXL technique, the demarcation line was well defined in all cases with a mean depth of 219 ± 27.3 μm. There was a statistically significant difference in corneal demarcation line depth between transepithelial and epithelium-off techniques (P = 0.008 and P < 0.05). The shallower demarcation line in the transepithelial group suggests that it is less effective. Conclusion. Based on the depth of the demarcation line, the cross-linking effect of epi-off AXL seems more efficacious than after transepithelial AXL. The future will show if the biomechanical effect will be sufficient to stop progression of keratoconus similarly after standard CXL. This trial is registered with NCT04045626.